Plasmodium falciparum antigenic diversity: Evidence of clonal population structure - Rich, Stephen M. (The National Academy of Sciences of the USA, 1997)
Plasmodium falciparum, the agent of malignant malaria, is one of mankind’s most severe scourges. Efforts to develop preventive vaccines or remedial drugs are handicapped by the parasite’s rapid evolution of drug resistance and protective antigens. We examine 25 DNA sequences of the gene coding for the highly polymorphic antigenic circumsporozoite protein. We observe total absence of silent nucleotide variation in the two nonrepeated regions of the gene. We propose that this absence reflects a recent origin (within several thousand years) of the world populations of P. falciparum from a single individual; the amino acid polymorphisms observed in these nonrepeat regions would result from strong natural selection. Analysis of these polymorphisms indicates that: (i) the incidence of recombination events does not increase with nucleotide distance; (ii) the strength of linkage disequilibrium between nucleotides is also independent of distance; and (iii) haplotypes in the two nonrepeat regions are correlated with one another, but not with the central repeat region they span. We propose two hypotheses: (i) variation in the highly polymorphic central repeat region arises by mitotic intragenic recombination, and (ii) the population structure of P. falciparum is clonal—a state of affairs that persists in spite of the necessary stage of physiological sexuality that the parasite must sustain in the mosquito vector to complete its life cycle.